Discussion of Hedge Disclosures, Future Prices, and Production Distortions - Hayes, Rachel M. (Journal of Accounting Research, 2000)
Rachel M. Hayes, Discussion of Hedge Disclosures, Future Prices, and Production Distortions, Journal of Accounting Research, Vol. 38, Supplement: Studies on Accounting Information and the Economics of the Firm (2000), pp. 83-89